Biography of the Prophet in the narrations of Hashem bin Al-Qasim Al-Kanani - Al-Khulaifawi, Akram Abdul-Dawood; Enayat Saeed, Abeer (Al-Adab Journal, 2020)
The research aims to identify the biography of Imam Hashem bin Al-Qasim Al-Kanani and his narratives in the prophetic biography and the researcher used the historical descriptive approach because interest in history science began in the adult era, and this was represented by telling historical events related to the incidents that preceded the emergence and beginning of Islam and the Islamic state in Medina and the concomitant invasions The Prophet, in addition to the events that occurred in the days of the rightly caliphate, and this great effort was made by the media of the first Hijri century by documenting those events and their narration and making sure to collect them from the imams who narrated them or their contemporaries or were part of it.Hashem bin Al-Qasim was one of the imams who was keen on transferring, documenting and preserving historical narratives, and I will discuss in his research his biography and historical narratives in the Prophet’s biography, which was divided into two subjects and as he will come, relying in this on the most important sources and references approved in scientific and research studies